Gender role stereotypes as an ethical resource in the peruvian advertising discourse - Carbajal Obando, Ninowska Camila (2021)
The most renowned brands worldwide incorporate initiatives in their business approach that seek equality between genders in society. Nonetheless, brands in their advertising campaigns, gender remains stereotyped in the roles men and women play, which can be considered harmful to society and therefore unethical. Such discrepancy appears even in the same intervention generated by advertising specialists who define and design the communication of these brands. Therefore, this study seeks to identify the arguments used by Peruvian advertising professionals to justify the use of gender role stereotypes within the advertising discourse from an ethical perspective. A qualitative approach was selected as the research method for this study. In-depth interviews with 16 professional advertisers from different areas in charge of producing this type of communication. The lack of knowledge about the actual dimension of the harmful gender stereotypes impeded a de-bate to leave without arguments to those who believe that the use of stereotypes is ethical. Professional advertisers have lost part of the necessary connection with ethics and find it hard to deal with these dilemmas because they do not identify the damage caused by gender role stereotypes in society.